Simulation of Slightly Degraded Reinforced Concrete Shaft Lining in Thick Topsoil - Haijian Xie; Henglin Lv (Tehnički Vjesnik, 2020)
This paper simulates the degradation of a 20 m-tall shaft lining in thick topsoil at the vertical depth of 500 m. The simulation was carried out under the similarity theory. Three reduced scale models were prepared from the original structure. The first model was subjected to circumferential load and then cured naturally, the second model was subjected to circumferential load and then soaked in corrosive solution, and the third model was subjected to circumferential and vertical loads and then soaked in corrosive solution. Without changing the circumferential load, vertical load was applied to the three models until they failed. The three models were found to have similar failure patterns: the uniform cracks first appeared at the top and bottom of the outer lining; the concrete of the inner lining cracked, and the upper part of the shaft lining was crushed, showing a diagonal shear failure. Model 1 had greater cracking load and ultimate load than model 2 and model 3. This is because the coupling between vertical and circumferential loads induces micro-cracks between the inner and outer linings, and thus accelerates the corrosion of the RC shaft lining in the corrosive solution.